Effect of tagitinin C isolated from kembang bulan [Tithonia diversifolia (Hemsley) A. Gray] leaves on VEGF and TNF-α expressions ofkeloid fibroblast - Arif Yusuf Wicaksana; Dwi Aris Nugrahaningsih; Mae Sri Hartati Wahyuningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Tagitinin C, an active constituent of Tithonia diversifolia (Hemsley) A. Gray, has  been proven can inhibit the collagen deposition of keloid fibroblasts in vitro.  However, its mechanism of action has not been widely studied. One possible mechanism involves growth factors and cytokines. Vascular endothelial growth  factor (VEGF) and tumor necrosis factor alpha (TNF-α) play an important role  in the collagen deposition. The study aimed to evaluate the effect of tagitinin  C on VEGF and TNF-α expression in keloid fibroblasts culture. An experimental  laboratory study using fibroblast cell lines at passages III and IV was performed.  Treatments were divided into two groups i.e. the treatment groups after incubation with tagitinin C at various concentration of 1, 0.5, 0.25, and 0.125μg/ mL for 72 h, and the control group using culture media without tagitinin C.  Following after incubation, the VEGF and TNF-α levels of keloid fibroblast culture supernatant were measured by ELISA. Kruskal-Wallis test continued  using Mann-Whitney test or one way Anova continued by independent t test  were applied to evaluate the differences between groups. A p value of less  than 0.05 was considered statistically significant. The VEGF levels significantly  decreases in concentration-dependent manner after treatment of the tagitinin C at various concentrations (p<0.05). However, no significantly difference in  TNF-α levels was observed (p> 0.05). In conclusion, tagitinin C decreases the  VEGF expression of keloid fibroblasts. However, it has no effect on the TNF-α  expression.